Effect of Transcriptional Regulatory Factor FoxO3a on Central Nervous System Oxygen Toxicity - Zhang, Yanan; You, Benming; Chen, Yuliang; Yang, Junlin; Xie, Chengwei; Huang, Guoyang; Li, Runping; Hu, Ping (Frontiers in Physiology, 2020)
Central nervous system (CNS) oxygen toxicity (CNS-OT) is a toxic reaction that appears after the inhalation of gas at an excessive oxygen partial pressure during underwater operation or hyperbaric oxygen (HBO) treatment. The mechanism of CNS-OT has not been clearly characterized. Though it has been attributed to the excessive oxidative stress induced by HBO, evidences against this hypothesis have been reported. Here we find that Forkhead box protein O3 (FoxO3a) is important for CNS-OT protection. FoxO3a knock-out (KO) mice had a shorter latency to develop convulsions and greater number of seizures within a certain period of time. The acute lung injury (ALI) induced by CNS-OT was also more severe in FoxO3a KO mice. Further analysis reveals a significant decrease in the activity of catalase (CAT), an antioxidant enzyme and a significant increase in the content of malondialdehyde (MDA), an oxidative product, in brain tissues of FoxO3a KO mice. Short-time HBO exposure could increase FoxO3a expression level and trigger its nuclear translocation. The level of nuclear localized FoxO3a peaked at 8 hrs after exposure. Our results demonstrate that the activity of FoxO3a is highly sensitive to HBO exposure and FoxO3a plays important roles in protecting CNS-OT. Further mechanic analysis reveals that FoxO3a protects CNS-OT via activating antioxidative signaling pathway.